Bahasa Umpatan sebagai Ekspresi Emosional Gen Z: Analisis Penyalahgunaan Bahasa Indonesia dalam Kehidupan Sehari-hari - Aisha Arifa Arifin; Erina Zahwa Amelia Prasasti; Iftitah Rinda Aulia; Tasya Atiqotim Minnarika; Sutrisno Gustiraja Alfarizi; Roekhan Roekhan (LPPM Universitas Muhammadiyah Sumatera Barat, 2025)
The Indonesian language plays a central role as a tool of communication, a symbol of national unity, and a reflection of linguistic politeness in society. However, in practice, this ideal function often experiences deviation, one of which is through the use of impolite language in the form of swearing or profanity. This phenomenon has become increasingly common in various communication contexts, both offline and online, especially among younger generations. This study aims to describe the forms of Indonesian language misuse as swearing expressions, analyze the social and cultural factors influencing their use, and identify their linguistic and social impacts on politeness norms. The method used is quantitative descriptive which is then developed with qualitative descriptive to deepen the meaning of the quantitative results. Data were collected through observations using Google Form among Gen Z participants aged 18–25 years. The findings reveal three main categories of swearing expressions: literal, euphemistic, and contextual-humorous. Factors contributing to their use include emotional expression, social solidarity, peer influence, and the digital culture that encourages expressive communication styles. Although swearing sometimes functions as a marker of closeness or humor, it still poses a risk of degrading linguistic politeness and reshaping public communication patterns. This study highlights the importance of fostering polite language awareness through linguistic education and digital literacy to ensure that the Indonesian language continues to represent the nation’s identity and character in the modern era.Keywords: Indonesian language, swearing, language politeness, Gen Z, sociolinguistics